2008
DOI: 10.1002/hep.22486
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus–induced oxidative stress suppresses hepcidin expression through increased histone deacetylase activity

Abstract: Chronic hepatitis C is characterized by iron accumulation in the liver, and excessive iron is hepatotoxic. However, the mechanism by which hepatitis C virus (HCV) regulates iron metabolism is poorly understood. Hepcidin plays a pivotal role as a negative regulator of iron absorption. The aim of the current study was to elucidate the mechanisms that govern hepcidin expression by HCV. Huh 7 cells, Huh7. Iron is an essential metal that functions as a component of oxygen-carrying proteins and of redox enzymes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
198
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(219 citation statements)
references
References 39 publications
19
198
1
1
Order By: Relevance
“…Our findings, including the reduced hepcidin/ferritin ratio and correlation between hepcidin and ferritin concentrations fit well with reports showing that hepcidin induction was relatively impaired in CHC patients, but also that its regulation by iron stores was maintained (13,14). These findings are also in agreement with recent studies in animal and cellular models suggesting that HCV suppresses hepcidin production and may contribute to the development of iron overload in CHC (19,20).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings, including the reduced hepcidin/ferritin ratio and correlation between hepcidin and ferritin concentrations fit well with reports showing that hepcidin induction was relatively impaired in CHC patients, but also that its regulation by iron stores was maintained (13,14). These findings are also in agreement with recent studies in animal and cellular models suggesting that HCV suppresses hepcidin production and may contribute to the development of iron overload in CHC (19,20).…”
Section: Discussionsupporting
confidence: 92%
“…However, in most cases, hepcidin was found suppressed during chronic HCV infection, 12,13 possibly because of ROS-mediated reduction in HAMP gene expression. 14 On the other hand, HCV-driven inflammation may counteract ROS-induced hepcidin repression, since elevated IL-6 stimulates HAMP gene transcription. 15 This second level of dichotomy merely stresses our incomplete understanding of the nature of the interactions between HCV and iron homeostasis at various disease stages.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC6 has also been implicated in the establishment of chronic infection of HCV. Miura et al have demonstrated that chronic HCV infection induces the accumulation of reactive oxygen species and subsequently evokes HDAC activity, which, in turn, deacetylates histones and regulates the location and activities of hypoxiainducible factors, CCAAT/enhancer binding protein a and signal transducers and activators of transcription 3 to suppress the expression of hepcidin, a key negative regulator of iron availability [137]. Sustained low hepcidin expression may contribute to the elevated iron accumulation in the liver and chronic hepatitis.…”
Section: Facilitating Viral Pathogenesismentioning
confidence: 99%